Implementasi Agile Organization di Sektor Publik: Studi Kasus Kementerian Energi dan Sumber Daya Mineral - Hendris Agung Prasojo; Muhammad Aswad; Bambang Utoro (Jurnal Wacana Kinerja)
This research aims to identify the variables influencing the success of organisasi agile implementation in the Ministry of Energy and Mineral Resources (KESDM), thereby developing a conceptual framework for agile implementation in the Ministry of Energy and Mineral Resources (KESDM).